Primary Amoebic Meningoencephalitis in an Iranian Infant. (26th July 2012) - Movahedi, Zahra; Shokrollahi, Mohammad Reza; Aghaali, Mohammad; Heydari, Hosein
Abstract : Introduction . Naegleria fowleri, a free living amoeba, can cause devastating and deadly diseases in humans. This is the first report of primary amoebic meningoencephalitis from Iran. Case report . A five-month-old male infant presented with the history of fever and eye gaze for three days, after beginning of bacterial meningitis, a plain and contrast CT revealed communicated hydrocephalus. In the repeat of CSF analysis on microscopic examination of wet preparation of CSF, Naegleria Fowleri was seen. Then, Amphotericin B and Rifampin were started. On followup, two months later, the patient was totally asymptomatic. Conclusion . Though occurrence of PAM is rare, this unusual disease has grave prognosis, so infection with free living amoebas must be considered in differential diagnosis of pediatric patients of purulent meningitis without evidence of bacteria on Gram's stain and imaging findings, nonspecific brain edema on CT or hydrocephalus even without history of contact.